Microgrid Power Quality Indices Performance Incorporating Renewable Energy Resources and FACTS Devices - Honey Baby, J. Jayakumar, Shanty Chacko (International Journal of Advanced Science and Technology, 2020)
Microgrids (MG) integrated with the distributed generation (DG) results enhancing the reliability, prominence of energy supply, diminishing power loss and reduced carbon emission. Besides, renewable energy resources are now getting more heed due to their environmental impacts. Despite enormous benefits, there are a plethora of challenges persisting due to the integration of DG resources in MG. Power quality (PQ) events sorted the first among the challenging index. Voltage profile management has become a demanding text in microgrids. This paper depicts voltage profile management in microgrid using different power quality scenarios associated with incorporation of Renewable Energy Resources and FACTS Devices (SVC and DSTACOM). A 6 bus microgrid test-bud system used for the examination. A new power quality index introduced, termed as Voltage Qualified Degree (VQD). The proposed work achieves the required indices like Total Harmonic Distortion (THD) and voltage stability performances in different buses. Finally, the mitigation of harmonics achieved to an optimal rate as well as stability enhancement attained using FACTS devices projected in the paper. Keywords: Microgrid; Distribution Generation; Power Quality; Voltage Qualified Rate; FACTS Devices.